Organizational and Legal Principles of Ensuring Academic Autonomy of Higher Educational Institutions - Yevdokimenko, S. V.; Євдокименко, С. В.; Inshyn, M. I.; Іншин, М. І.; Salmanova, O. Y.; Салманова, О. Ю.; Polstyanoy, A.; Полстяной, А.; Olena Salmanova (Amazonia Investiga. – 2020. – Vol. 9, Issue 32(August). – P. 55-60, 2020)
Визначено зміст та особливості організаційно-правових засад забезпечення академічної автономії закладів вищої освіти. Сформовано авторські визначення таких понять як «академічна автономія навчальних закладів», «організаційне забезпечення академічної автономії» та «правове забезпечення академічної автономії». Розглянуто історичні етапи становлення та розвитку академічної автономії. Охарактеризовані зарубіжні та міжнародні норми щодо дотримання академічної свободи та доброчесності у найбільш розвинених демократичних країнах світу. Надано пропозиції з удосконалення академічної мобільності, академічної автономії та академічної свободи як в Україні, так і в світі.

The objective of the article is to determine the content and specific features of organizational and legal principles for ensuring the academic autonomy of higher educational institutions. In order to achieve this objective, the authors used the following methods of scientific cognition: dialectical, formal and legal, bibliographic. Problematic issues that are directly related to the implementation of legal norms for ensuring academic autonomy of higher educational institutions have been studied. The authors have formed own definitions of such concepts as “academic autonomy of educational institutions”, “organizational provision of academic autonomy” and “legal provision of academic autonomy”. Historical stages of formation and development of academic autonomy have been considered. Foreign and international norms regarding the observance of academic freedom and honesty in the most developed democratic countries of the world have been characterized. Suggestions for improving academic mobility, academic autonomy and academic freedom both in Ukraine and in the world have been provided.

Определены содержание и особенности организационно-правовых основ обеспечения академической автономии заведений высшего образования. Сформированы авторские определения таких понятий как академическая автономия учебных заведений, организационное обеспечение академической автономии и правовое обеспечение академической автономии. Рассмотрены исторические этапы становления и развития академической автономии. Охарактеризованы зарубежные и международные нормы соблюдения академической свободы и добродетели в наиболее развитых демократических странах мира. Даны предложения по усовершенствованию академической мобильности, академической автономии и академической свободы как в Украине, так и в мире.
Організаційно-правові засади забезпечення академічної автономії закладів вищої освіти
Principios organizativos y legales para garantizar la autonomía académica de las instituciones de educación superior
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; вища освіта; higher education; высшее образование; академічна автономія; academic autonomy; академическая автономия; правові засади; legal principles; правовые основы; законодавство; legislation; законодательство; правове забезпечення; legal support; правовое обеспечение; навчальні заклади; educational institutions; учебные заведения; зарубіжний досвід; foreign experience; зарубежный опыт; publikatsii u WoS